The New Production of Expert Knowledge Education, Quantification and Utopia - Grek, Sotiria (Palgrave Studies in Science, Knowledge and Policy, 2024)
This Open Access book offers a novel perspective on the role of quantification in the making of education utopias through an analysis of expert knowledge and its producers. Drawing on empirical findings from the European Research Council funded project 'International Organisations and the Rise of a Global Metrological Field' (METRO, 2017-2022), Education, Quantification and Utopia focuses on the ways that metrological realism has constructed a well-supported epistemic infrastructure, built on relationships and practices that go beyond the mere objectivity and reliability of numerical evidence. The book's chapters outline how the production of new forms of education expertise have led to ideational and institutional interdependencies, and ultimately the making of an intricate, fragmented and opaque knowledge and governance web.